Translation Ideologies of The Culture Specific Items in Indonesian Translation “Of Mice and Men” Novel - Martinda Intan Permatahati; Abdurrachman Faridi; Mursid Saleh (International Conference on Science, Education, and Technology, 2021)
Translating a novel is an activity that requires making a great number of decisions and consequently carries many risks of making mistakes. All decisions made by translators in the translation process depend on the translator's ideology. The focus of this research is the ideology of the Indonesian translation of the novel "Of Mice and Men". Since the novel carries a lot of American Culture, the researcher wants to analyze the ideology used by the translator. The most difficult problem is how to find some unfamiliar words or sentences in the target text (TT). A translator must be able to find several possibilities covering the diversity of translation strategies that can solve CSI translation problems. In the translation study, the translation of Culture-Specific Items (CSI) becomes an obstacle for translators. This study aims to describe the types of CSI, CSI translation techniques, and the translator's ideological tendencies. This research is descriptive qualitative. Data was obtained using content analysis. The data is in the form of words and phrases. Data collection was done manually from the novel Of Mice and Men and an Indonesian translation entitled “Tikus dan Manusia”. Experts' judgment will provide comments to maintain the validity of the data. The data are categorized based on several theories. The first is the CSI theory proposed by Newmark (1998), the translation strategy proposed by Davies (2003), and Venuti (1995) about translation ideology.